(untitled) (Marketing Journal, 2025)
The agricultural sector is of great importance in ensuring the sustainable growth of the national economy based on the socio -economic development of the regions. In particular, agrologistics centers are being established in a number of regions of the count ry. Marketing and logistics are equally necessary in the development of agrologistics. Therefore, in this article, the author addresses the issue of developing agrologistics centers in the regions based on the principles of marketing and logistics. The art icle covers the organization of agrologistics infrastructure and agrologistics systems based on the principles of marketing and logistics.